2023
DOI: 10.3390/ma16124223
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Fatigue Crack Propagation of a Forging Die Made of Chromium–Molybdenum–Vanadium Tool Steel on Its Durability

Marek Hawryluk,
Marzena Lachowicz,
Aneta Łukaszek-Sołek
et al.

Abstract: The paper presents the results of tests on a die insert made of non-standardised chrome-molybdenum–vanadium tool steel used during pre-forging, the life of which was 6000 forgings, while the average life for such tools is 8000 forgings. It was withdrawn from production due to intensive wear and premature breakage. In order to determine the causes of increased tool wear, a comprehensive analysis was carried out, including 3D scanning of the working surface; numerical simulations, with particular emphasis on cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The element analysis at a normal load of 150 N and a wear time of 20 min is shown in Figure 11 b. The microanalysis indicated that the wear was more severe, and intense plastic deformation occurred in the wear scars [ 38 , 39 ]. Fractures and deep furrows were visible in the wear scars.…”
Section: Resultsmentioning
confidence: 99%
“…The element analysis at a normal load of 150 N and a wear time of 20 min is shown in Figure 11 b. The microanalysis indicated that the wear was more severe, and intense plastic deformation occurred in the wear scars [ 38 , 39 ]. Fractures and deep furrows were visible in the wear scars.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of works describing the impact of inclusions on steel durability analyze hard steels, most often bearing and tool steels (this is the same group of steels) [27][28][29][30][31][32]. In these steels, almost every brittle inclusion is a structural micro-notch, which is the focus of the crack.…”
Section: Introductionmentioning
confidence: 99%